Temporal changes in fecal indicator bacteria and potential waterborne pathogens at Sequiota Spring: from sewer to spring - Durstock, William J.; Owen, Marc R.; Mirza, Babur S. (Frontiers in Microbiology, 2025)
Waterborne pathogens from human fecal material pose significant health risks in karst environments, where water can easily infiltrate springs, rivers, and streams via old, leaky septic tanks and damaged sewer lines. We collected 24 samples over three summers and one winter to monitor fecal indicator bacteria (FIB) and potential waterborne pathogens in Sequiota Spring using Microbial Source Tracking (MST) and Illumina paired-end sequencing of bacterial 16S rRNA gene amplicons. MST indicated a significant reduction (46 times) in human fecal indicator bacteria (HFIB), particularly Bacteroides dorei, from 2020 to 2022. Similarly, 16S rRNA gene sequencing showed a decline in B. dorei sequences, from 56% of all Bacteroidetes sequences in 2020 to just 4% of all retrieved Bacteroidetes sequences in 2022. Furthermore, 16S rRNA gene sequences within the Enterobacteriaceae and Arcobacteraceae families, related to the genera E. kobei and A. cryaerophilus also showed a decline after repair work. In contrast, sequences related to Legionella, remained consistent throughout the study. Winter 2019 HFIB levels were similar to summer 2019, indicating comparable pre-repair contamination. Waterfowl-associated FIB remained low (~300 cells/L) and stable from 2019 to 2022, suggesting that sewer repairs were the primary driver of HFIB reduction. These results suggests that repairing old sewer infrastructure substantially reduced human fecal contamination and decreased the presence of potential waterborne pathogens, improving water quality. This study highlights the effective application of molecular techniques under field conditions in identifying and addressing nonpoint source human fecal contamination at Sequiota Spring.